Assessment of antiemetic and modulatory activity of dihydrocoumarin on copper sulfate induced emetic chicks: An in vivo investigation - Kajal Kumari Sharma; Md. Sakib Al Hasan; Razina Rouf; Yasin Emon; Emon Mia; Rakib Hossan; Md. Arif Hossain; Md. Nasimul Haque Shipon; Muhammad Torequl Islam (Food Chemistry Advances)
Dihydrocoumarin (DHC) is a natural compound found in plants like sweet clover and tonka beans, commonly used as a flavoring agent in food and as a fragrance in cosmetics. This study investigates the potential antiemetic properties of DHC using a copper sulfate-induced emesis model using 2-day-old Gallus domesticus chicks. Administered at doses of 12.5, 25, and 50 mg/kg, DHC's impact was compared with standard antiemetics; domperidone (DOM, 7 mg/kg) and ondansetron (OND, 5 mg/kg) were administered orally as positive controls. Results demonstrated that DHC significantly (p < 0.05) reduced the frequency of retches and prolonged the latency period in a dose-dependent manner. At 50 mg/kg, DHC achieved the highest latency (54.92 ss) and maximum reduction in retches (24.38), highlighting its standalone efficacy. However, combination therapies revealed antagonistic effects when DHC (50 mg/kg) was co-administered with DOM or OND, emphasizing the complexity of potential drug interactions. Despite its moderate efficacy compared to standard drugs, acute toxicity testing, conducted according to OECD guidelines, revealed no adverse effects at doses up to 1000 mg/kg, suggesting an LD50 greater than 1 g/kg in chicks. DHC exhibited promise as a natural antiemetic with a milder profile.